(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Around the world, HIV/AIDS infects nearly half of all victims of AIDS-related illnesses. In Somalia, 10,500 persons are thought to be living with HIV/AIDS. A 500-person estimate of children who are HIV-positive is also available. According to estimates, only 35% of HIV-positive persons go to ART centres for their medicine due to lack of awareness. Therefore, this study was designed to assess level of awareness about HIV/AIDS among people living in Galmudug, Somalia. MATERIALS AND METHODS: A cross-sectional design was used to assess the degree of HIV and AIDS awareness among residents of Galmudug, Somalia. The study population consisted of reproductive-aged males and females (15 to 45 years old), and respondents were drawn using a purposive sampling technique. The structured questionnaire was developed to collect the information by interview method. A descriptive and inferential statistical analysis was performed using IBM SPSS version 25 software. RESULTS: This study found that most Somalians had moderate-to-adequate knowledge about HIV/AIDS (57.8%), whereas 42.2% had poor knowledge. A total of 274 (78.3%) of the samples showed a poor attitude toward HIV/AIDS, while 76 (21.7%) displayed a positive attitude toward the disease. An association was also found between marital status (χ2 = 10.07, p< 0.05) and education level (χ2 = 29.55, p< 0.05) and knowledge of HIV/AIDS. In relation to attitude towards awareness of HIV/AIDS, demographic variables (marital status, age, occupation, and education) were significantly associated. CONCLUSIONS: The community needs to provide factual and precise knowledge of HIV/AIDS through aggressive awareness and door-to-door campaigns on the prevalence of the virus.